Assessment of urban thermal stress by UTCI – experimental and modelling studies: an example from Poland - Błażejczyk, Krzysztof; Kuchcik, Magdalena; Błażejczyk, Anna; Milewski, Pawel; Szmyd, Jakub (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
The paper presents a new approach to the study of the spatial variability of heat stress in urban areas. The Universal Thermal Climate Index UTCI was applied for this purpose. The spatial variability of UTCI at the local scale was studied using examples of urban areas with different sizes and geographical locations. The experimental research on urban heat stress was conducted in Warsaw. The research covers both differences between UTCI in urban to rural areas as well as the variation of heat stress within small residential districts in Warsaw. We found a very large and significant heat stress gradient between downtown Warsaw and rural stations. Spatial variability of UTCI was also observed in microclimate research. A modelling approach was presented based on examples from Warsaw, a city with a population of almost 2 million, as well as examples from several spa towns with populations of up to 40,000 located in various parts of Poland. GIS analysis (ArcGIS for Desktop and IDRISI) was applied for this purpose.